The controlled synthesis of g-C3N4/Cd-doped ZnO nanocomposites as potential photocatalysts for the disinfection and degradation of organic pollutants under visible light irradiation. Issue 4 (7th January 2021) - Sher, Mudassar; Javed, Mohsin; Shahid, Sammia; Iqbal, Shahid; Qamar, Muhammad Azam; Bahadur, Ali; Qayyum, Muhammad Abdul
Abstract : The controlled design of novel Z-scheme g-C3 N4 /Cd-ZnO heterojunction via chemical co-precipitation technique. 60% g-C3 N4 hybridized with 7% Cd-doped ZnO (g-C3 N4 /Cd-ZnO) NCs have been proved to be optimum visible-light-driven (VLD) photocatalysts. Abstract : The in situ growth of well-dispersed Cd-doped ZnO nanoparticles (Cd-ZnO NPs) on graphitic carbon nitride (g-C3 N4 ) nanosheets was successfully achieved through the co-precipitation method for the formation of Cd-doped ZnO nanocomposites with g-C3 N4 (Cd-ZnO/g-C3 N4 NCs). The effect of different compositions of ternary nanocomposites (Cd-ZnO/g-C3 N4 NCs) on photocatalytic properties was investigated. Ternary NCs, in which 60% g-C3 N4 hybridized with 7% Cd-doped ZnO (g-C3 N4 /Cd-ZnO) NCs were proven to be optimum visible-light-driven (VLD) photocatalysts for the degradation of methylene blue (MB) dye. The enhanced photodegradation of MB is mainly due to the increase in the generation of photogenerated charge carriers (reactive oxygen species (ROS), O 2−, and ˙OH radicals). The electron spin resonance (ESR) experiment revealed that the superoxide and hydroxyl radicals were the leading species responsible for the degradation of MB. Moreover, the NC exhibited tremendous stability with a consistently high MB degradation rate for 10 successive catalytic cycles. The structural and optical properties of CdO, ZnO NPs, Cd-ZnO NPs, g-C3 N4 NSs, and g-C3 N4 /Cd-ZnO NCs were investigated via XRD, SEM, EDX, TEM, FTIR spectroscopy, UV-Vis spectroscopy, ESR spectroscopy, and PL spectroscopy techniques. The synthesized photocatalysts were also applied against Gram-positive and Gram-negative bacterial strains to evaluate their antibacterial activities.